Beta endorphins - molecules of therapeutics - T.g, Shrihari (The European Research Journal, 2020)
Endorphins are endogenous morphine, neuropeptides produced in the pituitary gland. There are three types of endorphins beta-endorphins, enkephalins, and dynorphins. Beta-endorphins are an abundant endorphins synthesized and stored in the anterior pituitary gland; it is a precursor of POMC (Proopiomelanocortin). Beta-endorphins has got various mechanisms of actions such as anti-inflammatory activity, analgesic activity, stress buster activity, and immune stimulatory activity can be used to treat various diseases such as chronic inflammatory diseases such as heart disease, Alzheimer’s disease, cancer, auto-immune disease, diabetes mellitus, and aging. This article highlights about the basic research findings of beta-endorphins and mechanisms of actions in management of various diseases.